Optimization Of Polyphenols Recovery From Defatted Roselle Seed Using Microwave Assisted Extraction - Yusoff, Nurul Izyatulikma (2017)
Roselle is well known for its calyces that are used to prepare herbal beverages, jams and jellies because it has been long recognized as a source of antioxidants. However, roselle seeds in the velvety capsules are usually discarded as waste despite the fact that they contain good nutritional constituents. This is due to the limited exploitation of their usefulness and benefits as a potential alternative for human food source. Therefore, this study aims to determine the yield content, total phenolic content and total flavonoid content of defatted roselle seed extract prepared using microwave assisted extraction (MAE). MAE has not been applied in the extraction of roselle seed to the best knowledge, therefore this study is important. In this work, polyphenols were extracted using ethanol-water (70 % (v/v)) in a closed vessel under microwave irradiation with and without temperature control. The influence of different parameters on the extraction process (extraction time (min), microwave power (W), solvent to solid ratio (mL/g), extraction temperature (°C)) were studied. Response surface methodology (RSM) was used to develop predictive models and optimization of the polyphenols recovery process. Without temperature control, the predicted MAE conditions of 10 min, 300 W and 97.7178 mL/g resulted in high yield (65.0367 ± 1.2450 %) and phenolic content (18.2244 ± 0.3310 mg GAE/g) due to the reaching of subcritical state. However, low flavonoids content (6.4524 ± 0.3035 mg QE/g) was unexpectedly obtained due to extract degradation at 163 C. On the other hand, the optimum conditions of MAE with temperature control (12 min, 290 W, 125 mL/g and 150 °C) were also identified to yield the highest phenolic (21.0950 ± 0.4907 mg GAE/g) and flavonoid content (8.9452 ± 0.1873 mg QE/g). The optimum MAE extract with temperature control contains similar phenolic content to the extracts of maceration and Soxhlet, but the yield and flavonoid content increased 173 % and 443 %, respectively than the Soxhlet extracts. Gas chromatography-mass spectrometry analysis was further used to investigate the possible compounds available in the optimum extract. 1,2-epoxyhexadecane and palmitic acid were the major compounds found in the optimized extract for MAE with temperature control and MAE without temperature control, respectively. Thus, MAE appears to be a potential alternative for polyphenols recovery from roselle seed as it offers short extraction duration and high quality of extract.